Revision of the Bengalia torosa Wiedemann, 1819 species-group (Diptera: Calliphoridae), with notes on the systematic position of B. robertsi Kurahashi, 1987 and B. subnitida James, 1964 - Rognes, Knut (Zootaxa, 2018)
The mainly Oriental Bengalia torosa Wiedemann species-group is revised on the basis of males. Species concepts are based on male terminalia. Monophyly of the species-group is established on the basis of two unique synapomorphies of the distiphallus. Eleven species are recognized as valid, viz. Bengalia chekiangensis Fan, 1965, Bengalia chiangmaiensis Kurahashi & Tumrasvin, 1979, Bengalia concava Malloch, 1927, Bengalia escheri Bezzi, 1913, Bengalia fuscipennis Bezzi, 1913, Bengalia jejuna (Fabricius, 1787), Bengalia kanoi Kurahashi & Magpayo, 2000, Bengalia martinleakei Senior-White, 1930, Bengalia recurva Malloch, 1927, Bengalia torosa (Wiedemann, 1819), Bengalia xanthopyga Senior-White, 1924, and their geographical distributions are updated. The following new synonymies are proposed: Bezzigalia rivanella Lehrer, 2005 is a junior synonym of B. escheri, syn. nov.; Bengalia siamensis Senior-White, 1924, Gangelomyia kosungana Lehrer, 2007 and G. laoziella Lehrer, 2007 are junior synonyms of B. fuscipennis, syn. nov.; Gangelomyia evafoneae Lehrer, 2005 and G. senausmarta Lehrer, 2005 are junior synonyms of B. jejuna, syn. nov.; Gangelomyia indipyga Lehrer, 2005, G. philipyga Lehrer, 2005, G. schiavoae Lehrer, 2005, G. shivanella Lehrer, 2005, G. tagaloga Lehrer, 2005 and G. phantastika Lehrer, 2007 are junior synonyms of B. kanoi, syn. nov.; Gangelomyia gandhiana Lehrer, 2005 and G. krishna Lehrer, 2005 are junior synonyms of B. martinleakei, syn. nov.; Laoziana camerina Lehrer, 2005, L. mandarina Lehrer, 2005 and L. singhasaria Lehrer, 2005 are junior synonyms of B. recurva, syn. nov. Lectotypes are designated for Musca favillacea Walker, 1859 and Bengalia escheri Bezzi, 1913. A male syntype of Musca torosa Wiedemann, 1819 has been located in NHMD and a female syntype of the same nominal species has been located in NMW. A male specimen in NHMD is proposed as neotype for Musca jejuna Fabricius, 1787, to replace the three existing female syntypes. A male specimen in NHMD is proposed as neotype for Musca torosa Wiedemann, 1819, to replace the newly located syntypes. The ICZN Commission will be requested, in a forthcoming paper, to formally set aside the existing name-bearing types of both nominal species and designate the proposed specimens as neotypes, in order to preserve the current usage of both names. Musca favillacea Walker, 1859 is removed from synonymy with Bengalia jejuna and treated as an unplaced name in the Bengalia torosa species-group. Bengalia robertsi Kurahashi, 1987 is removed from the Bengalia torosa species-group and re-assigned to the Bengalia labialis Robineau-Desvoidy species-group. Bengalia subnitida James, 1964 is assigned to the Bengalia peuhi Villeneuve species-group even though it lacks discal setae on the fifth abdominal tergite. Two new terms are introduced for description of the distiphallus of the B. torosa species-group. Bengalia recurva Malloch is reported for the first time from China.